Subclinical right ventricle systolic dysfunction in childhood-onset systemic lupus erythematosus: insights from two-dimensional speckle-tracking echocardiography. (May 2015) - Leal, G N; Silva, K F; França, C M P; Lianza, A C; Andrade, J L; Campos, L M A; Bonfá, E; Silva, C A
Objective: The objective of this article is to evaluate right ventricle strain imaging by two-dimensional speckle-tracking (2DST) in childhood-onset systemic lupus erythematosus (c-SLE). Methods: Thirty-five c-SLE patients with no signs or symptoms of heart failure and 33 healthy volunteers were evaluated by standard echocardiogram and 2DST. Conventional parameters included tricuspid annular plane systolic excursion (TAPSE), RV tissue-Doppler-derived Tei index and systolic pulmonary artery pressure. Global peak longitudinal systolic strain (PLSS) and strain rate (PLSSR) of RV were obtained by 2DST. Demographic/clinical features, SLEDAI-2K/SLICC/ACR-DI and treatment were also assessed. Results: The median current age was similar in patients and controls (14.75 vs. 14.88 years, p = 0.62). RV PLSS was significantly reduced in c-SLE (−24.5 ± 5.09 vs. −27.62 ± 3.02%, p = 0.003). Similar findings were observed after excluding patients with pulmonary hypertension (−24.62 ± 4.87% vs. −27.62 ± 3.02%, p = 0.0041). RV PLSS was positively correlated with TAPSE ( r = +0.49, p = 0.0027) and negatively correlated with Tei index ( r = − 0.34, p = 0.04) in c-SLE. RV PLSSR was not different comparing patients and controls (−0.65 s −1 ± 0.47 vs. −1.87 ± 0.49 s −1, p = 0.07). Further analysis of c-SLE patients revealed higher frequencies of neuropsychiatric manifestations (39% vs. 0%, p = 0.007) and antiphospholipid antibodies (55% vs. 18%, p = 0.035) in those with RV PLSS ≤ −23.7% vs >−23.7%. No differences were evidenced in demographic data, disease activity/damage or treatments ( p > 0.05). Conclusions: The present study, using a new and more sensitive technique, revealed subclinical RV systolic dysfunction in c-SLE patients that may have future prognostic implications. The novel association of asymptomatic RV dysfunction with neuropsychiatric manifestations and antiphospholipid antibodies may suggest common physiopathological pathways.